1995
DOI: 10.1152/ajprenal.1995.269.6.f806
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosatetraenoic acid is formed in response to EGF and is a mitogen in rat proximal tubule

Abstract: Hydroxyeicosatetraenoic acid (20-HETE) is a major cytochrome P-450-arachidonic acid metabolite in the rat kidney, and its synthesis along the nephron is specifically localized to the proximal tubule, where receptor density for epidermal growth factor (EGF) is the highest. EGF stimulated endogenous 20-HETE formation in a concentration and time-dependent manner, i.e., from 1.6 to 2.6 +/- 0.3 and 3.0 +/- 0.6 pmol 20-HETE.mg-1.min-1 at 10(-8) and 10(-7) M EGF, respectively. The effect of 20-HETE on proximal tubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 0 publications
2
64
0
1
Order By: Relevance
“…20-HETE has been reported to play an important role in the regulation of cerebral vascular tone by regulating the open state probability of calcium-activated potassium channels (32). It also promotes the formation of oxygen radicals (15,16,20,33,36,59) and contributes to endothelial dysfunction (35,42,45,49,62). More recently, inhibitors of the synthesis of 20-HETE have been reported to reverse the fall in cerebral blood flow (CBF) following subarachnoid hemorrhage (SAH) (3,21,28,35,55) and reduce infarct size following transient cerebral ischemia (35,42,45,57).…”
mentioning
confidence: 99%
“…20-HETE has been reported to play an important role in the regulation of cerebral vascular tone by regulating the open state probability of calcium-activated potassium channels (32). It also promotes the formation of oxygen radicals (15,16,20,33,36,59) and contributes to endothelial dysfunction (35,42,45,49,62). More recently, inhibitors of the synthesis of 20-HETE have been reported to reverse the fall in cerebral blood flow (CBF) following subarachnoid hemorrhage (SAH) (3,21,28,35,55) and reduce infarct size following transient cerebral ischemia (35,42,45,57).…”
mentioning
confidence: 99%
“…epithelial cell proliferation; epidermal growth factor receptor; cell signaling 20-HYDROXYEICOSATETRAENOIC acid (20-HETE) is a lipid metabolite of arachidonic acid that is produced by -hydroxylase enzymes of the cytochrome P-450 4A (CYP4A) and 4F families (21). 20-HETE has long been known to play an integral role in the regulation of renal function, including renal vascular tone (14), tubuloglomerular feedback (49), autoregulation of renal blood flow (12,13,48), tubular transport (6,30,38,45), and mitogenesis (4,18,23,44).There has been renewed interest in 20-HETE because of its potential as a novel therapeutic target in the treatment of acute kidney injury (32), cancer (8 -10), and polycystic kidney disease (PKD) (28,29). Regner et al (32) showed that acute administration of a 20-HETE mimetic resulted in increased renal protection following ischemia-reperfusion injury.…”
mentioning
confidence: 99%
“…5) A number of studies have demonstrated that 20-HETE has potent biological activities which contribute to the regulation of renal tubular and vascular function and the long-term control of arterial blood pressure. [6][7][8][9][10] 20-HETE is also a potent vasoconstrictor in the cerebral microcirculation and a regulator of vascular tone and autoregulation of cerebral blood flow. [11][12][13][14] On the other hand, EETs have been known as vasodilators and inhibitors of sodium and water transport in the kidney.…”
mentioning
confidence: 99%